2000
DOI: 10.1108/09593840010339835
|View full text |Cite
|
Sign up to set email alerts
|

The Internet and socio‐economic development: exploring the interaction

Abstract: The Internet and socioeconomic development : exploring the interaction Originally published in Information technology and people, 13 (2). pp. 85-101

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
137
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(139 citation statements)
references
References 13 publications
2
137
0
Order By: Relevance
“…Katz (1986) noticed that in many developing countries, noticeable trends towards achieving an information economy in terms of the number of people engaged in informationrelated occupations. However, he also brought evidence to suggest that, in developing countrie s, an increase in the number of information workers is a sign of underdevelopment rather than prosperity (Katz, 1986;Madon, 2000). These earlier findings support our observations with regards to H3.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Katz (1986) noticed that in many developing countries, noticeable trends towards achieving an information economy in terms of the number of people engaged in informationrelated occupations. However, he also brought evidence to suggest that, in developing countrie s, an increase in the number of information workers is a sign of underdevelopment rather than prosperity (Katz, 1986;Madon, 2000). These earlier findings support our observations with regards to H3.…”
Section: Resultssupporting
confidence: 82%
“…As observed by Madon, most organizations in developing countries are striving to achieve operational efficiency rather than to restructure their processes towards improved effectiveness. In the telecommunications sectors of such economies, it is commonplace to have large armies of technical workers to cope with the provision of administrative services in the light of dramatic increases in population, as well as to absorb surplus educated workers due to lack of capacity in the industrial sectors (Madon, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Lloyd-Ellis [58] confirmed that the spread of Information and Communication Technologies (hereinafter "ICT") increases worker productivity and lessens income disparity. Madon [59] claimed the requirement to afford wider connectivity that would increase global information infrastructure and support positive changes in socio-economic development. Accordingly, Leung [60] reported a significant association between Internet connectedness and information literacy.…”
Section: The Impact Of Infrastructure and Technology On Sustainable Ecomentioning
confidence: 99%
“…Heeks and Keeny (2002) argue that ICT is increasing divergence between the rich and the poor countries rather than supporting a 'catch up'. While exploring the interaction between the Internet and key dimensions of development, Madon (2000) finds evidence that the return on ICT investment in developing countries' organisations is dissatisfactory, and those organisations should have capacity to restructure themselves to promote efficiency and effectiveness.…”
Section: Introductionmentioning
confidence: 99%